POLARIS: a Building Block for Blackboard to Support Collaborative Learning - Lutgens, Gaby; Koehorst, André; Ronteltap, Frans (Proceedings of the International Conference on Networked Learning, 2004)
The Maastricht University (UM) has a leading role in the development of and research on Problem Based Learning (PBL), both nationally as well as internationally. Within this educational context students work in small learning teams (tutorial groups of about 12 students), acquiring, communicating, and integrating information in a process that resembles that of (scientific) inquiry. In practice, instead of attending weekly class lectures, students attend tutorial group meetings twice a week, monitored by a staff member (the tutor) who guides the group process. Within these groups, students are presented case-studies to solve over a period of six to eight weeks. The university works continuously to maintain its prominent and leading position in the field of educational renewal. One way to put this into practice is to uphold a system of thorough quality control. Within this framework a survey study was performed which gave insight in how students and staff evaluated this small-team learning. Outcomes stated that one was really enthusiastic about attending small group sessions (as usual at the UM with mainly problem based curricula) and to take one’s own responsibility to actively participate, both during meetings as in between the meetings when students spend time searching and studying information individually to add new perspectives. On the other hand, students stated they missed feedback on their information search activities. They seemed to lack the skill to find, search and evaluate literature to solve the problems. The survey also revealed that students did find it very fruitful to exchange ideas and bring together perspectives on a topic, but thought the time during the meetings was too short to go into depth. In other words, they missed the opportunity to (sufficiently) interact with each other (Ronteltap & Eurelings, 1996, 2002). This, while interactions in a group and the exchange of information are thought to be the basis of individual knowledge: knowledge develops through social interaction. Dillenbourg (1999) states that students do not learn from each other merely by solving the same problem at the same time, but because they interact (e.g. by explaining something or by negotiating about several solutions). Baker (1999) adds that only constructive interaction can lead to learning: interaction leading to (co)construction of understanding, insight, solutions and sometimes even (new) knowledge. When students participate in mutual discussions, make comparisons of each other's work and give their comments, search (individually) for information on the web and subsequently distribute the retrieved information in the group, and, when necessary, negotiate on the solutions to questions or tasks, this will, according to a lot of studies, lead to the (collaboratively) building of knowledge (Collins & Stevens, 1983, Scardamalia & Bereiter, 1996, Oxford, 1997, Norman, 1998). For this reason the UM started with pilot studies to support the interaction and learning processes within the tutorial groups by implementing ICT-tools. At first (in the mid nineties) one experimented with threaded discussions. Results were promising, but the functionality proved to be very limited. Very soon students and tutors lost overview on the discussion, one was not able to link contributions or reuse (parts of) documents. Subsequently the focus has been put on the development and evaluation of POLARIS, a tool specifically designed to support specific activities (a.o. writing, co-editing, reacting) that are needed for collaborative learning.